Outside Collateral, Preserving the Value of Inside Collateral and Sorting - Dorothea Schaf̈er (Schmalenbach Business Review, 2001)
Within a framework of debt renegotiation and a priori private information, what is the role of outside and inside collateral? The literature shows that unobservability of the project's returns implies that the high-risk borrower is more inclined to pledge outside collateral than is the low-risk borrower. However, this finding does not hold when the bank can observe neither the project's returns nor the borrower's risk class. We show that in this scenario, low-valued outside collateral enables the low-risk entrepreneur to select himself, but high value outside collateral has no sorting potential at all. We also show that a bank's incentive to sort borrowers may induce investment to preserve the value of the inside collateral and to build up restructuring know-how. If self-selection via outside collateral is operating, restructuring know-how reduces the cost of separation. If outside collateral gives rise to pooling, restructuring know-how may restore sorting.
Keywords: D82; G21; G33; 330; asymmetric information; restructuring know how; adverse selection